A Mixed-method Study of the Relationship between Students’ Interaction and Motivation in Medical Students - Qureshi, Sumair Nasim (Indus Journal of Bioscience Research, 2025)
Objective: The objective of this study was to explore the factors influencing medical students' learning experiences, with a specific focus on the role of teachers in the relationship between students’ interaction and motivation in medical students. Methods: A mixed-methods sequential explanatory design was employed. In the quantitative phase, 185 MBBS students from Shifa College of Medicine completed a structured questionnaire assessing factors affecting their learning. Data were collected for the duration of six months, from January 2024 to June 2024 and were analyzed using descriptive statistics. The qualitative phase involved two focus group discussions with volunteer students to explore their perceptions in greater depth. Thematic analysis was used to interpret qualitative data. Results: Quantitative results showed that 68.5% of students agreed or strongly agreed that teachers inspired them to learn, while 64% felt burdened by the extensive curriculum. Only 34.5% of students reported that classroom environments were conducive to learning. Emotional and peer support factors scored higher in mean values compared to teacher-related factors. Qualitative findings echoed these results, highlighting the critical role of enthusiastic teachers, the challenges posed by curriculum overload, the negative impact of poor physical facilities, and the importance of peer networks for emotional well-being. Conclusion: Teachers play a vital role in motivating medical students; however, effective learning also depends on manageable curricular loads, supportive physical environments, and strong emotional and peer support systems. Addressing these areas collectively can enhance student satisfaction, motivation, and academic performance in medical education settings.